PENDAMPINGAN PSIKOTERAPI ZIKIR PADA PECANDU SABU/METAMFETAMIN (STUDI NEURO-SEMANTICS TERHADAP PESERTA RUMAH TRANSFORMASI KOMUNITAS TAUBATERS 205) - Darwis Hude; Arwindo Arwindo; Ahmad Kamaludin; Puput Lestari (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Psychotherapy reciting the prayer of the Prophet Ayyub in surah Al-Anbiya/21 verse 83 can be a solution in rehabilitating methamphetamine addicts. By using the Prophet Ayyub's prayer as a medium for zikr, rehabilitation participants at the Taubaters 205 community transformation house can reflect on their condition with the Prophet Ayyub's condition when saying the prayer. Through meta-coaching, rehabilitation participants can give meaning to everything that happens in their lives. Then, you can reflect on the patience and wisdom of the Prophet Ayyub towards himself. Through gratitude, devotion, and sincere worship, carrying out obligatory and sunnah worship during the rehabilitation period to reduce the effects of methamphetamine addiction. This research uses neuro-semantic studies as an assessment and hypnotherapy to map the psychological indicators of rehabilitation participants into a matrix. Rehabilitation participants who have recovered from methamphetamine addiction will show changes in their level of efficacy. The results of this research show that zikr psychotherapy can provide psychological effects by changing indications in the intentions, meaning, self, power, other, state, time, and world of methamphetamine addicts. From a neuro-semantic perspective, addicts can be declared cured if they have the determination and strength to fight triggers when using methamphetamine. After carrying out zikr psychotherapy, rehabilitation participants have a strong belief system and meaning towards Allah, the Almighty Giver of Healing. However, recovery from addictive methamphetamine addiction is usually long-term. Addicts of methamphetamine can be said to have recovered if they have been able to overcome their addiction physically and are no longer dependent on the substance permanently. The psychological conditions and negative impacts experienced by methamphetamine addicts are different for each person. Therefore, former addicts must continue to do zikr even after leaving rehabilitation